Pengembangan Aplikasi Penerimaan Siswa Baru dengan Menggunakan Pemrograman Visual Basic 2010 dan Database MYSQL pada Kursus Primagama Bukittinggi - Mardison - (RJOCS (Riau Journal of Computer Science), 2016)
Has done research on Primagama Bukittinggi. From these studies can be found to the problem is slowness in data processing that takes a long time to generate the data quickly and accurately. To that made the development of the new system, in order to improve the efficiency and effectiveness of work in Bukittinggi Primagama with the use of the Visual Basic programming language and MySQL database supported.